2023
DOI: 10.1021/acs.orglett.3c00144
|View full text |Cite
|
Sign up to set email alerts
|

Organoelectrophotocatalytic C–H Silylation of Heteroarenes

Abstract: An organoelectrophotocatalytic approach for the C−H silylation of heteroarenes through dehydrogenation crosscoupling with H 2 evolution has been developed. The organoelectrophotocatalytic strategy is carried out under a simple and efficient monocatalytic system by employing 9,10-phenanthrenequinone both as an organocatalyst and as a hydrogen atom transfer (HAT) reagent, which avoids the need for an external HAT reagent, an oxidant, or a metal reagent. A variety of heteroarenes can be compatible in satisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 62 publications
2
33
0
Order By: Relevance
“…Based on the above results and our previous investigation, 20 a possible mechanism for the organophotoelectrochemical silylation cyclization of N -methyl- N -phenyl-2-(trifluoromethyl)acrylamide ( 1 ) with t BuMe 2 SiH ( 2 ) is proposed (Scheme 5). In the beginning, the irradiation of PQ with 420–425 nm LEDs produces excited PQ*.…”
Section: Introductionmentioning
confidence: 79%
“…Based on the above results and our previous investigation, 20 a possible mechanism for the organophotoelectrochemical silylation cyclization of N -methyl- N -phenyl-2-(trifluoromethyl)acrylamide ( 1 ) with t BuMe 2 SiH ( 2 ) is proposed (Scheme 5). In the beginning, the irradiation of PQ with 420–425 nm LEDs produces excited PQ*.…”
Section: Introductionmentioning
confidence: 79%
“…Upon light excitation, photoelectrochemical HAT catalysis can proceed via type-II or type-III mechanisms. In the type-II mechanism (Figure d), the excited photocatalyst (PC*) abstracts hydrogen atoms from R–H to give alkyl radicals (R • ), and this process is closely related to the direct photoinduced HAT. , The major difference is that the photocatalyst (PC) is regenerated via anodic oxidation of (PC • )–H. The type-III mechanism (Figure e) generates a hydrogen atom abstractor (Cl • or N +• ) through sequential anodic oxidation and photoexcitation, , and the hydrogen atom abstractor then triggers the HAT process.…”
Section: The Electrochemically Driven Hat Mechanism and Differences B...mentioning
confidence: 99%
“…Recently, Wang and co-workers reported an organo-electrophotocatalytic C–H silylation of heteroarenes by merging photochemistry and electrochemistry (Scheme 38 ). 58 This direct dehydrogenative C–H silylation relies on the dual function of 9,10-phenanthrenequinone (PQ) as a photo-electrocatalyst and a hydrogen atom transfer (HAT) reagent, and thereby avoids the requirement for metal reagents and traditional oxidants. Using the standardized reaction conditions, Wang showed that differently substituted quinolines, isoquinolines, pyridines, pyridazine, pyrimidine and other types of heterocycles gave the corresponding silylated products in good yields and excellent regioselectivity.…”
Section: C–h Bond Silylation With Silyl Radicalsmentioning
confidence: 99%